Proposal of a Conditioning Activity Model on Sprint Swimming Performance - de Arruda, Tarine Botta; Barbieri, Ricardo Augusto; de Andrade, Vitor Luiz; Cursiol, Jônatas Augusto; Kalva-Filho, Carlos Augusto; Bertucci, Danilo Rodrigues; Papoti, Marcelo (Frontiers in Physiology, 2020)
This study aimed to propose a conditioning activity (CA) model to stimulate improvement on neuromuscular responses, mechanical parameters and for the 50-m freestyle swimming. Thirteen male swimmers (19 ± 3 years and performances of 77% in relation to World Championship records) performed four CA protocols followed by a maximum performance in the 50-m freestyle. In the first protocol (P1) swimmers performed a standard warm-up ( 15 min); in the second protocol (P2) lunges (3 x 85% of the one-repetition maximum); in the third (P3) pull-ups (3 maximum repetitions) and box jumps 40 cm high and 60 cm deep (1 x 5 with 10% of the corporal weight); and in the fourth protocol (P4) a combination of exercises from the second and third protocols. CA protocols had no effect on the standard warm-up. However, P2 performance (27.01 ± 1.25 secs) was similar to P1 (27.01 ± 1.18 secs) and presented higher positive effects in mechanical parameters for the swim start performance in comparison to other protocols, contributing to improvements in the 50-m freestyle. In addition, turnaround time also had a negative effect, mainly in P3 (3.12 ± 0.28 secs), signalling the improvement of this variable in all protocols (P1: 3.30 ± 0.38 secs; P2: 3.17 ± 0.30 secs; P4: 3.17 ± 0.34 secs). P2 (after: 80 ± 11 %; before: 82.7 ± 9.9 %) and P3 (after: 82.7 ± 9.9 %; before: 85.1 ± 9.7 %) presented a possible positive effect on the percentage of voluntary activation in relation to P1 (after: 79.3 ± 10.7 %; before: 76.3 ± 12 %). In conclusion, the proposed conditioning activity protocols were not efficient for performance improvement in the 50-m freestyle compared to the standard model and seem to specifically influence each phase of the event.